1982
DOI: 10.1007/bf00282589
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rate of digestion of foods and post-prandial glycaemia

Abstract: The amount of carbohydrate released at 1 and 5 h by digestion in vitro of 2 g carbohydrate portions of 14 foods by human digestive juices was compared with the area under the 2-h blood glucose response curve when 50 g carbohydrate portions were fed to groups of five to ten healthy volunteers. A significant relationship was found between the amounts of sugars and oligosaccharides liberated at 1 and 5 h and the food blood glucose area expressed as a percentage of the blood glucose area for 50 g glucose (r = 0.86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(131 citation statements)
references
References 27 publications
8
121
1
1
Order By: Relevance
“…This confirms previous observations [8,[16][17][18][19][20] and supporting the concept of a direct relationship between the rate of carbohydrate absorption and glycaemic response, GIP release and insulin secretion. In this context it is important to note that, despite the lower glycaemic response when fat was co-ingested with pota-toes, the post-prandial insulin response was not significantly reduced.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms previous observations [8,[16][17][18][19][20] and supporting the concept of a direct relationship between the rate of carbohydrate absorption and glycaemic response, GIP release and insulin secretion. In this context it is important to note that, despite the lower glycaemic response when fat was co-ingested with pota-toes, the post-prandial insulin response was not significantly reduced.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the aim of the present study was to examine the acute interaction of two components of the high-carbohydrate, high-fibre diet: slowlyabsorbed carbohydrate, and fat. The effect of co-ingestion of fat on the post-prandial glucose, insulin and GIP responses to a rapidly-absorbed carbohydrate (potato) and a slowly-absorbed carbohydrate (lentils) [8] was measured. The secretion of GIP is greatly stimulated by fat ingestion as well as glucose and has been implicated in the entero-insular axis [9][10][11][12][13].…”
mentioning
confidence: 99%
“…Studies have indicated that heat processing renders some amount of starch fractions resistant to mammalian enzymes and thus escape digestion. Retrogradation of amylose is reported to lead to the formation of resistant starch (Jenkins et al 1982). It has been demonstrated that intermittent heating and cooling cycles significantly increased resistant starch fraction in wheat (Ranhotra et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…A major feature that appears to determine the metabolic effect of grain products and starchy foods is the rate at which these starchy foods are digested (Jenkins et al, 1980b). Carbohydrate food, which is more slowly digested, results in reduced glucose and insulin responses (O'Dea et al, 1981;Jenkins et al, 1982). Slowly digested starchy foods appear to be either lipid neutral or to reduce concentrations of triglycerides and low-density lipoprotein (LDL) cholesterol without significant reductions or even increased concentration of high-density lipoprotein (HDL) cholesterol (Jenkins et al, 1987b, c;Fontvieille et al, 1988Fontvieille et al, , 1992Wolever et al, 1992a, b;Miller, 1994).…”
Section: Introductionmentioning
confidence: 99%